The importance of a physical training protocol to improve the quality of life of people with HIV/AIDS (Research, Society and Development, 2023)
Prescribing physical activity for people with HIV/AIDS can delay the onset or prevention of many chronic diseases, improving heart function, reducing blood pressure and improving functional capacity is noted after just a few weeks of exercise. Practicing strategies used by physical education professionals can help develop mental, physical and emotional awareness. Given these benefits, the role of a physical education professional in monitoring individuals with HIV/AIDS has been increasingly discussed. Low levels of physical activity are common during the treatment period and have been associated with negative health outcomes. Therefore, understanding the barriers and facilitators of physical activity in people living with HIV/AIDS can improve the development and implementation of individual interventions aimed at improving physical activity. Therefore, the objective of this research is to verify whether physical exercise improves the quality of life, body composition and longevity of people living with HIV. The work is a Literature review, which corresponds to a method where it is possible to select already prepared materials, such as books, scientific articles, publications from official bodies. With the development of the research, it was possible to understand the objective of the physical education professional's role in monitoring people with HIV/AIDS is to contribute to the recovery of patients, which can directly impact recovery and quality of life.